Bisnis Jual Beli Online (Online Shop) dalam Hukum Islam dan Hukum Negara - Dewi Santri; Dermilan Siregar (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
The aim of this study is tounderstand online retail from an Islamic perspective (ie according to Islamic law). This research is descriptive quantitative. This study includes literature to examine written sources such as scientific journals, reference books, literature, encyclopedias, scientific articles, and other sources that are relevant and related to the focus of the study. Regarding the subject matter of the study in the form of texts or papers that describe and explain online stores/businesses that are increasingly popular in Indonesia.According to the findings of this study, Islam conducts online business according to Islamic law. Yes, there is an element of fraud, fraud, injustice and mismanagement. The Prophet said that buying and selling is legal as long as it is agreed upon (Antaradhin), both for retail sales and through online businesses, because it has a positive impact on buyers because it is convenient, fast and easy. Operation of online business is not permitted if it does not comply with the terms and conditions previously described.